2010
DOI: 10.1242/jeb.040378
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine promotes rhythmicity but not synchrony in a bilateral pair of bursting motor neurons in the feeding circuit of Aplysia

Abstract: ) modulatory actions on the spontaneous burst activity of the bilaterally paired B67 pharyngeal motor neurons (MNs). OA increased B67's burst duration and the number of impulses per burst. These effects reflected actions of OA on the intrinsic tetrodotoxin-resistant driver potential (DP) that underlies B67 bursting. In addition to its effects on B67's burst parameters, OA also increased the rate and regularity of burst timing. Although the bilaterally paired B67 MNs both exhibited rhythmic bursting in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…The prominent neuronal cluster was only found near the dorsal surface of the cerebral ganglion. This observation is almost consistent with a report on the CNS of Aplysia (Martínez‐Rubio et al, ), although a single TBH‐IR neuron found in the visceral ganglion of Limax (Figs. A, A) seems to be lacking in the abdominal ganglion of Aplysia .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prominent neuronal cluster was only found near the dorsal surface of the cerebral ganglion. This observation is almost consistent with a report on the CNS of Aplysia (Martínez‐Rubio et al, ), although a single TBH‐IR neuron found in the visceral ganglion of Limax (Figs. A, A) seems to be lacking in the abdominal ganglion of Aplysia .…”
Section: Discussionsupporting
confidence: 93%
“…However, different numbers of OA‐IR neurons have been reported in studies on the buccal ganglia of other gastropod animals. Elekes et al () reported more than 10 OA‐IR neurons in Lymnaea , whereas Vehovszky et al () and Martínez‐Rubio et al () reported only 3 OA‐IR neurons in Lymnaea and Aplysia . These discrepancies may be explained partly by species differences, and partly by differences in the methods used (immunohistochemistry of OA vs. immunohistochemistry and in situ hybridization of TBH).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation